2021
DOI: 10.1016/j.ejim.2021.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Refining age stratum of the C2HEST score for predicting incident atrial fibrillation in a hospital-based Chinese population

Abstract: Background:The C 2 HEST score (C 2 : coronary artery disease [CAD] / chronic obstructive pulmonary disease [COPD] (1 point each); H: Hypertension; E: Elderly (Age≥75, doubled); S: Systolic heart failure (doubled); T: Thyroid disease (hyperthyroidism)) has been validated to predict incident atrial fibrillation (AF). Its performance in the hospital-based Chinese population has never been evaluated. Methods: Risk factors for incident AF were investigated in a hospital-based population. Comparison of the C 2 HEST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Patients ≥ 75 years of age are at increased risk of recurrence. In a recent study by Li et al it was found that the modified mC2HEST score (with age ≥ 65 years added as 1 point) increased the predictive power for atrial fibrillation ( 28 ). However, from our results, this was not observed for postoperative recurrence of AF.…”
Section: Discussionmentioning
confidence: 99%
“…Patients ≥ 75 years of age are at increased risk of recurrence. In a recent study by Li et al it was found that the modified mC2HEST score (with age ≥ 65 years added as 1 point) increased the predictive power for atrial fibrillation ( 28 ). However, from our results, this was not observed for postoperative recurrence of AF.…”
Section: Discussionmentioning
confidence: 99%
“…We found also that the percentage of AHRE ≥3 min increased with increasing HATCH score. Recently, Li et al ( 19 ), in China, modified the mC 2 HEST score (adding age ≥65 years as one point), which increased the predictive accuracy and discriminative capability for incident AF. We also evaluated the performance of the mC 2 HEST score but found it not as suitable as the HATCH score (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Atrial fibrillation (AF) is a leading arrhythmia worldwide and the major risk of systemic thromboembolic events (Hindricks et al, 2021 ; January et al, 2019 ). Several predicting models, including CHA 2 DS 2 ‐VASc score (Hu & Lin, 2018 ; Zuo et al, 2013 ), C 2 HEST score (Li, Bisson, et al, 2019 ; Li, Pastori, et al, 2019 ; Lip et al, 2020 ), mCHEST score (Li, Bai, et al, 2021 ), HAT 2 CH 2 score (Emren et al, 2016 ; Hu & Lin, 2017 ), and HAVOC score (Ntaios et al, 2020 ; Zhao et al, 2019 ) have been elucidated for predicting new AF in different populations and all revealed acceptable discriminating power. A prospective study enrolled 528 symptomatic arrhythmic patients and showed a CHA 2 DS 2 ‐VASc score with a C statistic 0.63 and an optimal cutoff at 2 for new‐onset AF (Zuo et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…C 2 HEST score was used to predict new AF in a Danish Healthy Population (Lip et al, 2020 ), post‐stroke patients from France, (Li, Bisson, et al, 2019 ) and Chinese and Korean subjects (Li, Pastori, et al, 2019 ). The mCHEST score was refined in a hospital‐based Chinese population and showed better predictive performance than other predicting models for incident AF (Li, Bai, et al, 2021 ). HAT 2 CH 2 score has a slightly but significantly better predictive performance than CHA 2 DS 2 ‐VASc score for new AF in cancer patients (Hu & Lin, 2017 ), and can be used to predict the development of AF in patients after coronary artery bypass surgery (Emren et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%